ANALISIS EFEKTIVITAS ORGANISASI DINAS KEPENDUDUKAN DAN PENCATAN SIPIL KABUPATEN WONOGIRI - Azhar Ar Rahman, Zakaria; Subowo, Ari; Santoso, R. Slamet (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2025)
The Population and Civil Registration Office has an important role because it brings public services closer to the community. However, the Population and Civil Registration Office is often faced with complex problems, especially managerial problems. This study aims to examine the relationship between leadership with organizational effectiveness, motivation with organizational effectiveness, and leadership and motivation with organizational effectiveness. This research uses a correlational quantitative method, with data collection techniques of interviews, questionnaires, observation, and documentary with primary and secondary data sources. The results of this study indicate that Leadership (X1) has a positive and significant relationship to Organizational Effectiveness (Y) of the Population and Civil Registration Office of Wonogiri Regency. So that the better the leadership, the better the organizational effectiveness. Motivation (X2) has a positive and significant relationship to Organizational Effectiveness (Y) of the Population and Civil Registration Office of Wonogiri Regency. So that the better the motivation, the better the organizational effectiveness. Simultaneously Leadership (X1) and Motivation (X2) have a significant relationship to Organizational Effectiveness (Y). So that if leadership and motivation are improved, it will also increase organizational effectiveness.